Apple polyphenol inhibits colon carcinoma metastasis via disrupting Snail binding to focal adhesion kinase. (January 2015) - Hung, Chia-Hung; Huang, Chi-Chou; Hsu, Li-Sung; Kao, Shao-Hsuan; Wang, Chau-Jong
Highlights: Apple polyphenol suppressed motility of colon cancer cell DLD-1. Apple polyphenol regulated focal adhesion kinase (FAK) and its signaling cascades. Snail direct binding to a putative E-box contributed to the FAK regulation. Apple polyphenol in vivo inhibited adhesion and metastasis of DLD-1 cell. Abstract: We investigated inhibitory effects of apple polyphenol (AP) in vitro and in vivo . AP significantly suppressed migration, invasion, colony formation and adhesion of DLD-1 cells. AP also reduced expression of tubulin and F-actin, and consequently altered the cytoskeleton structure. AP reduced expression of focal adhesion kinase (FAK) but not talin, α-actinin and vinculin. The activation of FAK downstream effectors paxillin, Src, PI3K and Akt were also inhibited by AP. Moreover, AP inhibited activity but not expression level of FAK-associated GTPase Rac-1, Cdc42 and Rho A. The inhibition of FAK expression by AP was proteasome-independent, which was attributed to interfered binding of Snail to a putative E-box on the FAK promoter. Anti-tumoral and anti-metastatic effects of AP were also demonstrated in vivo . Collectively, AP significantly inhibited motility of DLD-1 cells via disruption of interaction between Snail and the FAK promoter and consequently diminished tumorigenesis and metastasis of DLD-1 cells.